2013
DOI: 10.1155/2013/987910
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of Pectoralis Major Ruptures in Rodeo Steer Wrestlers

Abstract: Background. Pectoralis major tendon ruptures have been reported in the literature as occupational injuries, accidental injuries, and sporting activities. Few cases have been reported with respect to rodeo activities. Purpose. To describe a series of PM tendon ruptures in professional steer wrestlers. Study Design. Case series, level of evidence, 4. Methods. A retrospective analysis of PM ruptures in a steer wrestling cohort was performed. Injury data between 1992 and 2008 were reviewed using medical records fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…Hanna et al 11 reported similar results, with higher peak torque, work, and return to sport in surgically treated patients compared with nonoperatively treated patients. In contrast, Zvijac et al 43 and Lau et al 20 did not find differences in return to sport and satisfaction in their patients, although they did not conduct objective measurements of strength.…”
Section: Comparative Outcomesmentioning
confidence: 82%
See 2 more Smart Citations
“…Hanna et al 11 reported similar results, with higher peak torque, work, and return to sport in surgically treated patients compared with nonoperatively treated patients. In contrast, Zvijac et al 43 and Lau et al 20 did not find differences in return to sport and satisfaction in their patients, although they did not conduct objective measurements of strength.…”
Section: Comparative Outcomesmentioning
confidence: 82%
“…As reported in the literature, the most common causes of pectoralis major rupture were identified to be bench press in 49% (300/608) of cases, contact sports in 8% (47/608), and weight lifting in 7% (41/608). Pooled results from 10 studies 2,6,10,11,15,16,18,20,28,30 suggest that 90% (134/149) of patients successfully returned to playing sports after isolated pectoralis major tendon repair at a mean time of 6.1 ± 1.7 months (range, 4-8.5 months) ( Table 1). Of these patients, 8 studies 6,10,11,15,16,18,28,30 reported that 74% (95/128) successfully returned to their preinjury level of sport.…”
Section: Return To Activity Injury Cause and Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pectoralis major muscle is a large and powerful triangular muscle in the chest that originates from the anterior surface of the sternum and the sternal portion of the clavicle, coming together into the pectoralis major tendon, which inserts into the humerus bone of the upper arm. 1,6,11,21 Pectoralis major ruptures can occur in several parts of the muscle—the junction between the tendon and the humerus, the junction between the muscle and the tendon, in the muscle belly, or at the junction of the muscle and the sternum. 1,4,6 Most surgical series have focused primarily on the tendon injuries.…”
mentioning
confidence: 99%
“…De acordo com Vasconcelos et al (2003) e Lau et al (2013), o esforço exacerbado realizado pelos membros superiores pode levar à ruptura do tendão ou até mesmo do ventre muscular do peitoral maior, entretanto também pode ocorrer devido a uma queda do animal, quando o atleta cai sobre os braços estendidos.…”
Section: Artigos Originais -Promoção Da Saúdeunclassified